Large Cell Neuroendocrine Carcinoma of the Ampulla of Vater - Beggs, Rachel E; Kelly, Michael E; Eltayeb, Omer; Crotty, Paul; McDermott, Ray; Ridgway, Paul F (JOP. Journal of the Pancreas, 2012)
Context Large cell neuroendocrine carcinomas of the ampulla of Vater are rare and confer a very poor prognosis despite aggressive therapy. There are few case reports of large cell neuroendocrine carcinomas of the ampulla of Vater in the literature and to date no studies have been done to establish optimal management. We describe a pooled case series from published reports of neuroendocrine carcinomas of the ampulla of Vater including a case which presented to our institution. Methods A narrative review was undertaken including all published English case reports of large cell neuroendocrine carcinomas of the ampulla of Vater. Our primary outcome was to determine the overall survival. Results Twenty cases of large cell neuroendocrine carcinomas of the ampulla of Vater were identified. Seventy-six percent of patients were reported to have died of disease with a mean survival of 11.8 months. Twenty percent of the tumours were associated with an adenoma. The approximate median survivals were 15 months for those with an associated adenoma and 11 months without. Conclusions This pooled analysis demonstrates both the rarity and poor prognosis of large cell neuroendocrine carcinomas of the ampulla of Vater. Although surgical resection is the mainstay of treatment, we review common adjuvant chemotherapy regimes. Prognosis may be improved when these tumours are associated with adenomas, however, further studies are needed. Image: Circumferential fleshy ulcerated tumour.